Pisces, Anegada Bay protected area, Buenos Aires province, Argentina - Llompart, Facundo Manuel (2010)
We provide the first list of marine fish from Anegada Bay, a coastal protected area in Buenos Aires Province. Fish records were obtained from gillnets and recreational fishery captures. Thirty seven species belonging to 29 families and 18 orders were identified. The most numerous order was Perciformes with eight families and 10 species. Odontesthes argentinensis, Micropogonias furnieri, Cynoscion guatucupa and Mustelus schmitti were verified in all sampling sites and the last two were the most represented either in the experimental fishing and recreational captures. Presence of Lagocephalus laevigatus extended the so far known range distribution of this fish species, representing the southernmost records in Argentinean coastal waters. The fish fauna composition from Anegada Bay could be considered as from a transitional zone.